PENGGUNAAN METODE RECIPROCAL TEACHING DALAM MENINGKATKAN KEMAMPUAN READING COMPREHENSION SISWA KELAS X MADRASAH ALIYAH NEGERI MOJOKERTO TAHUN PELAJARAN 2016-2017 - Rodli, Moh (Balai Diklat Keagamaan Surabaya, 2018)
This paper reports a study on the use of Reciprocal Teaching Methodwhich aimed to improve the reading comprehension of the tenth yearstudents of MAN Mojokerto. The method applied in this study was acollaborative classroom action research which involves 46 students inthe academic year of 2016/2017. This study was conducted in twocycles by following the procedures of the action research: planning,implementing, observing, and reflecting. Each of which encompassedtwo meeti ngs. The data of the study were gathered throughobservation checklists, field notes, and reading test. The findings ofstudy showed that Reciprocal Teaching Method can improve thestudents’ reading comprehension. The improvement could be seenfrom the increase of the number of students who got score < 70. Besides,Reciprocal Teaching Method can increase the students’ involvementduring the teaching and learning process.